Sodium-Carboxymethylcellulose/Polyphenol-Gossypol-Carboxymethylcellulose Copolymer Films for Ocular Drug Delivery: Preparation and Physico-Chemical Properties - Khaydar Ergashovich, Yunusov; Abdushkur Abdukhalilovich, Sarymsakov; Akobirkhon Ibodullo O`g`li, Shukurov; Jamoliddin Nasiriddinovich, Todjiyev; Abdumutalib Abdupatto Ugli, Atakhanov; Jiang, Guohua; O. Solomevich, Sergey (Asian Journal of Chemistry, 2022)
In present work, the formation of nanostructured antiviral biosoluble ophthalmic drug films composed of sodium carboxymethylcellulose/polyphenol-gossypol-carboxymethylcellulose copolymer is described. The biorelease time and physico-chemical parameters of the ophthalmic drug films were regulated by changes in the degree of substitution and polymerization of sodium carboxymethylcellulose and the pH value of its aqueous solutions. The morphology and size of the antiviral agent embedded in sodium carboxymethylcellulose films were determined by using atomic force microscopy and dynamic light scattering. The UV spectroscopy was used to observe drug release from the polymeric matrix and it was determined that the maximum drug release occurred after 24 h. By regulating the concentration of polyphenol-gossypol-carboxymethylcellulose copolymer antiviral substance in the polymer, the spherical nanoparticles with sizes of 5-24 nm and cubic nanoparticles with sizes of 46-95 nm were formed.